The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/genes13061014
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Protein Acidic and Rich in Cysteine as an Exercise-Induced Gene: Towards Novel Molecular Therapies for Immobilization-Related Muscle Atrophy in Elderly Patients

Abstract: Long periods of immobilization, among other etiologies, would result is muscle atrophy. Exercise is the best approach to reverse this atrophy. However, the limited or the non-ability to perform the required physical activity for such patients and the limited pharmacological options make developing novel therapeutic approaches a necessity. Within this context, secreted protein acidic and rich in cysteine (SPARC) has been characterized as an exercise-induced gene. Whereas the knock-out of this gene leads to a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…We also suggested that, considering SPARC mediates exercise-induced benefits [ 49 ], SPARC administration could represent a substitute to exercise [ 50 ]. This is of a specific importance especially for elderly patients who are not able to perform the required physical activity due to diseases, hospitalisation, or physical disabilities [ 51 ]. This would allow them to possibly receive some of the exercise benefits although they are not able to perform exercises.…”
mentioning
confidence: 99%
“…We also suggested that, considering SPARC mediates exercise-induced benefits [ 49 ], SPARC administration could represent a substitute to exercise [ 50 ]. This is of a specific importance especially for elderly patients who are not able to perform the required physical activity due to diseases, hospitalisation, or physical disabilities [ 51 ]. This would allow them to possibly receive some of the exercise benefits although they are not able to perform exercises.…”
mentioning
confidence: 99%
“…Briefly, studies using genetically-modified mice suggested that exercise-induced muscle phenotype changes are SPARC -dependent [ 18 ] and showed that SPARC overexpression mimics exercise effects in mice, whereas Sparc KO leads to an accelerated ageing phenotype which is improved by exercise [ 19 ]. Together, these data suggest that at least a part of the exercise benefits are mediated by SPARC , which would be anti-aging, and with effects against various metabolic disorders and age-related diseases [ 20 , 21 ]. SPARC is expressed in various situations and has even been suggested as a molecular physiological and pathological biomarker [ 22 ] for which its measure could optimize personalized medicine [ 23 ].…”
Section: Secreted Protein Acidic and Rich In Cysteine ( Spa...mentioning
confidence: 99%
“…Functional genomics explorations of obesity and the factors that impact its development (diet, exercise, etc.) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] have revealed specific related genes and improved our molecular understanding of obesity development.…”
Section: Modern Health Challenges and Obesitymentioning
confidence: 99%